MODEL PEMBELAJARAN TEMATIK DI MI/SD - Widyaningrum, Retno (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2012)
Abstract. In early age, it is generally asserted that all aspects of learnersâ intelligence like IQ, EQ, and SQ grow and develop extraordinarily. At this age, young learners will only see a real thing holistically and able to understand the relationship among the concepts simply. In accord to this, the learning process should be fitted with their needs and level of proficiency. Besides, it should be directed to help them learn the concrete objects with their real life experiences. On the contrary, if the learning process is conducted separately, this means that the learnersâ holistic thinking process is not well-developed and it makes them hard to learn optimally. The research revealed that the kindergarten learners who were taught thematically had better ability and readiness in joining the study than those who were not taught thematically. Based on the result, it could be justified that the learning process for young learners was more effective if it was managed integratively through a thematic approach.